A Comparison of Limited Liability Partnership Regulations in the State of Delaware, USA, Malaysia & India - Ayu Anezka Chandradevi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Departing from the absence of regulations related to Limited Liability Partnership in the legislation in Indonesia, with the formulation of the problem in the form of (1) How is the regulation of Limited Liability Partnership in Delaware, United States, Malaysia and India?, and (2) How is the comparison of the regulation related to Limited Liability Partnership in Delaware, United States, Malaysia and India?. It has been found that many countries in the world have adopted the rules of Limited Liability Partnership into their positive laws for a long time, such as the United States which is the originator then Malaysia and India. From this we can see that to the extent of regulation of Limited Liability Partnerships in ASEAN and Asian countries, Indonesia is among the countries that do not keep up with world developments and leave their people with a set of legal tools that tend not to meet the needs and interests of the public. It is known that the form of civil partnership in Indonesia that is most similar to the form of Limited Liability Partnership is the form of Persekutuan dengan Firma. However, the Persekutuan with Firma adopted in Indonesia still applies the concept of unlimited liability. This means that in the event of a loss suffered by a partnership with a firm due to the fault or negligence of one of the allies, the compensation will not only utilize the assets of the partnership with the firm but also the assets of the partners, even the innocent partners among the three countries under comparison. Actually all three have similarities with each other because they are both based on the regulatory model first adopted by the United States.